PARASITE DIVERSITY OF Hoplosternum littorale FROM THE TIETE-BATALHA RIVER BASIN, SOUTHEASTERN BRAZIL - Pelegrini, Larissa Sbeghen [UNESP]; Mirandola Dias Vieira, Diego Henrique [UNESP]; Rosa Leite, Lucas Aparecido [UNESP]; Giao, Thayana; Azevedo, Rodney Kozlowiski de; Abdallah, Vanessa Doro (Inst Pesca, 2021)
A total of 53 tamboatas, Hoplosternum littorale, from the Batalha River, Sao Paulo, southeastern Brazil, were examined between February 2014 to December 2016. Seventeen species of parasites were identified, and 961 specimens were collected. The richness of each community varied from one to seven species of parasites per fish. The metacercariae of Diplostomum lunaschiae showed higher prevalence and mean abundance, being the core species. Gyrodactylus sp. obtained a higher mean intensity value. Aporocotylidae gen. sp. showed a significant negative correlation between its abundance and the standard host weight and length, while Spiroxys sp. showed a significant negative correlation between its abundance and the host weight. The high parasitic diversity of this host in Batalha River confirm it is an important site for maintaining local biodiversity with a relevant contribution to the knowledge of freshwater biodiversity in the State of Sao Paulo. Gyrodactylidae gen. sp., Austrodiplostomum mordax, Aporocotylidae gen. sp., D. lunaschiae, Diplostomidae gen. sp. 1, Contracaecum sp., Dioctophyme renale, Porrocaecum sp., Pseudocapillaria sp. 1, Pseudocapillaria sp. 2, Spiroxys contortus, Oligobdella sp., and Lernaea cyprinacea are parasites mentioned for the first time in H. littorale. Aporocotylidae gen. sp., Gyrodactylidae gen. sp., and Oligobdella sp. are new species in process of taxonomic description by the authors of the present study.
Keywords: parasitic biodiversity; ecology; tamboata; fish parasites; freshwater fish; Sao Paulo